ANALISIS BAHASA POLITIK ANIES BASWEDAN DALAM PIDATO PENGUKUHANNYA SEBAGAI GUBERNUR JAKARTA PERIODE 2017-2022 - Dhea Tisane Ardhan (ETNOLINGUAL, 2020)
Related to the political aspect, language selection becomes a crucial element for the perpetrators. Political language can be considered to have a "purpose-oriented" or it orients towards certain goals. This study aims to find out the types of utterances based on JL Austin's perspective, the types of illocutionary act based on Searle's theory that emerged in the inaugural speech of Governor Anies Baswedan, and also the hidden ideology conveyed by Anies Baswedan by using the types of utterances and illocutionary acts that occur in his inaugural speech. The method used in this research was descriptive qualitative. Data from this study were obtained from Anies Baswedan's political speech which was delivered on 16 October 2017 at the City Hall of DKI Jakarta. The results of this study indicate that Anies Baswedan uses two types of utterances, namely assertive and performative. In addition, the type of illocutionary act that is most commonly found in Anies Baswedan's speech is assertive illocutionary act.Keywords: Political language, utterances, illocutionary acts